A lot of nothing [videorecording (DVD)] - Mo (Mo McRae); Kaplan, Sarah Kelly; Noel, Y'lan, 1988-; Coleman, Cleopatra, 1987-; Hartley, Justin, 1977-; Davis, Lex Scott, 1991-; Sardy, David (RLJ Entertainment, 2023)
James and Vanessa are ostensibly the perfect married couple; beautiful, successful, and smart. Their lives spiral out of control when they decide to seek justice against a neighbor they saw commit a crime on the evening news.